Sex-Dependent Anti-Stress Effect of an α5 Subunit Containing GABAA Receptor Positive Allosteric Modulator - Piantadosi, Sean C.; French, Beverly J.; Poe, Michael M.; Timić, Tamara; Marković, Bojan D.; Pabba, Mohan; Seney, Marianne L.; Oh, Hyunjung; Orser, Beverley A.; Savić, Miroslav M.; Cook, James M.; Sibille, Etienne (Frontiers in Pharmacology, 2016)
Rationale: Current first-line treatments for stress-related disorders such as Major Depressive Disorder (MDD) act on monoaminergic systems and take weeks to achieve a therapeutic effect with poor response and low remission rates. Recent research has implicated the GABAergic system in the pathophysiology of depression, including deficits in interneurons targeting the dendritic compartment of cortical pyramidal cells. Objectives: The present study evaluates whether SH-053-2'F-R-CH3 (denoted "α5-PAM"), a positive allosteric modulator selective for α5-subunit containing GABAA receptors found predominantly on cortical pyramidal cell dendrites has anti-stress effects. Methods: Female and male C57BL6/J mice were exposed to unpredictable chronic mild stress (UCMS) and treated with α5-PAM acutely (30 minutes prior to assessing behavior) or chronically before being assessed behaviorally. Results: Acute and chronic α5-PAM treatments produce a pattern of decreased stress-induced behaviors (denoted as “behavioral emotionality”) across various tests in female, but not in male mice. Behavioral Z-scores calculated across a panel of tests designed to best model the range and heterogeneity of human symptomatology confirmed that acute and chronic α5-PAM treatments consistently produce significant decreases in behavioral emotionality in several independent cohorts of females. The behavioral responses to α5-PAM could not be completely accounted for by differences in drug brain disposition between female and male mice. In mice exposed to UCMS, expression of the Gabra5 gene was increased in the frontal cortex after acute treatment and in hippocampus after chronic treatment with α5-PAM in females only, and these expression changes correlated with behavioral emotionality. Conclusions: We showed that acute and chronic positive modulation of α5 subunit-containing GABAA receptors elicit anti-stress effects in a sex-dependent manner, suggesting novel therapeutic modalities.